Caps for sale - Slobodkina, Esphyr, 1908- (New York, Scholastic Inc. by arr. with Addison-Wesley, 1940)
The monkeys steal the peddler's caps while he is asleep.
Illustrated lining-papers in colors.
Keywords: Peddlers and peddling -- Fiction; Monkeys -- Fiction